Socio-Economic Status of Rural Women of Self Help Groups: A Study of Dhaniakhali and Polba-Dadpur Blocks of Hooghly District, W.B. - Kumar, Saheli; Goswami, Kaushalendra Prakash (National Geographical Journal of India, 2022)
Nowadays Self-Help Group or SHG plays a vital role not only in social transformation and upliftment of rural women but also in social-economic betterment of them. The main objective of this paper is to examine the impact assessment in the socio-economic status of rural women through Self Help Groups with the help of a micro-level study of two C. D. blocks namely Dhaniakhali and Polba-Dadpur in Hooghly district. 40572 SHGs are consisting of 394897 members in 18 C. D. blocks of Hooghly district. Among the blocks, Daniakhali and Polba-Dadpur were selected for the study, of which 28 groups are chosen randomly. From these selected groups 108 members have been selected to conduct the primary survey. Personal interviews were conducted to find out the major purposes of the study i.e. to examine the role of SHG in developing the socio-economic status of rural women and to analyse the impact of SHGs in decision making. The study is mainly based on primary data and simple per cent calculation is used for analysing the data. The major analytical tool employed for the study is tabular analysis to facilitate easy interpretation. Map of the study area is prepared through ArcGIS 10.5 software. The present study explains a detailed socio-economic profile of the SHG members in the study area